2015
DOI: 10.1194/jlr.m060053
|View full text |Cite
|
Sign up to set email alerts
|

ABCA1 contributes to macrophage deposition of extracellular cholesterol

Abstract: This article is available online at http://www.jlr.org it can be mobilized from these cells by components of the HDL system. In this process, either preformed plasmaderived HDL or HDL generated by cells such as macrophages within atherosclerotic plaques, function as acceptors of excess cellular cholesterol. Excess cellular cholesterol is believed to be transferred to HDL from either intracellular or plasma membrane pools of cholesterol.ABCA1 and ABCG1 both function in mediating cellular cholesterol effl ux and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 36 publications
(41 reference statements)
0
32
0
Order By: Relevance
“…The cells (2×10 6 cells/well) were transfected using Lipofectamine 2000 (Invitrogen) as previously described (16). The effeciency of transfection was examined bys by RT-qPCR and western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The cells (2×10 6 cells/well) were transfected using Lipofectamine 2000 (Invitrogen) as previously described (16). The effeciency of transfection was examined bys by RT-qPCR and western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, previously we showed that both ABCA1 and ABCG1 mediate macrophage deposition of extracellular cholesterol microdomains 4, 5 . Our finding here that ABCA1 is necessary for mobilization of this cholesterol demonstrates an interesting concerted action of ABCA1, both to deposit and then effect mobilization of extracellular cholesterol microdomains.…”
Section: Discussionmentioning
confidence: 56%
“…We have shown previously that ABCA1 and ABCG1 mediate macrophage deposition of cholesterol microdomains into the extracellular matrix 4, 5 . Thus, ABCA1 shows two separate functions; one that mediates deposition of the extracellular cholesterol microdomains, and another that mediates ApoA-I’s mobilization of the extracellular microdomains.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations